The Application of Ijtihâd Takhrîj in Contemporary Sharia Business - Agus Putra, Panji Adam (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
This research aims to elaborate on the concept of ijtihâd takhrîj, which was introduced by scholars to address evolving contemporary legal issues. It also seeks to analyze the application of ijtihâd takhrîj in the field of mu’âmalah mâliyyah or Islamic economic law. The approach used in this research is a normative juridical approach. This research is classified as a literature study and uses secondary data. The results of the study indicate that: first, ijtihâd takhrîj is crucial for realizing the efforts of ijtihâd to solve legal issues, including Islamic economic law, which is continuously developing; and second, in practice, ijtihâd takhrîj is applied to address contemporary legal issues in mu’âmalah mâliyyah activities. Some applications of ijtihâd takhrîj in contemporary sharia business such as law of commercial insurance, intellectual property rights, issues of inflation, law on giving discounts, law of travel checks, law of savings deposits, credit and debit cards, buying and selling via social media, law of compensatory payments in transactions, and Sharia-Based Financial Technology Peer-To-Peer Lending.